Neoadjuvant PD-1 Blockade Combined With Chemotherapy Followed by Concurrent Immunoradiotherapy in Locally Advanced Anal Canal Squamous Cell Carcinoma Patients: Antitumor Efficacy, Safety and Biomarker Analysis - Xiao, WeiWei; Yuan, Yan; Wang, SuiHai; Liao, Zhidong; Cai, PeiQiang; Chen, BaoQing; Zhang, Rong; Wang, Fang; Zeng, ZhiFan; Gao, YuanHong (Frontiers in Immunology, 2022)
Background Anal canal squamous cell carcinoma (ACSCC) is an exceedingly rare malignant neoplasm with challenges in sphincter preservation, treatment toxicities and long-term survival. Little is known concerning the activity of PD-1 antibodies in locally advanced ACSCC. This study reports on the efficacy and toxicities of a neoadjuvant PD-1 blockade combined with chemotherapy followed by concurrent immunoradiotherapy in ACSCC patients, and explores biomarkers for predicting treatment outcomes and describes mutation signatures. Methods In this cohort study, patients were treated as planned, including four cycles of neoadjuvant PD-1 antibody toripalimab combined with docetaxol and cisplatin, followed by radiotherapy and two cycles of concurrent toripalimab. Multiplex immunofluorescence staining with PD-L1, CD8, CD163, Pan-Keratin and DAPI was performed with the pretreatment tumor tissue. Whole exome sequencing was performed for the primary tumor and peripheral blood mononuclear cells. Response was assessed, and acute and late toxicities graded prospectively. Results Five female patients with a median age of 50 years old (range, 43-65 years old), finished treatment as planned. One patient had grade 3 immune related dermatitis. Four patients achieved a complete clinical response (cCR) after neoadjuvant treatment and the other patient also achieved a cCR after radiotherapy. All five patients were alive and free from disease and had a normal quality of life, with 19.6-24 months follow up. Biomarker tests revealed tumor PD-L1 expression and paracancerous stroma CD163 expression were positively correlated with tumor response in the neoadjuvant treatment phase. TMB, and TNB were not correlated with response. Three Sanger signatures were suggested. TTN, POLE, MGAM2 were the top mutation frequencies, and 80 significant driver genes were identified. Pathway analysis showed enrichment of apoptosis, Rap1, Ras, and pathways in cancer signaling pathways. Eight significantly deleted regions were identified. Conclusions This small sample of locally advanced ACSCC patients had quite good treatment outcomes, and a 100% sphincter preservation rate, after multimodality treatment with PD-1 antibody toripalimab and chemoradiotherapy. PD-L1 expression may serve as a predictive biomarker for this treatment strategy.